Amniotic fluid microbiota and metabolism with non-syndromic congenital heart defects: a multi-omics analysis - Wenli Xu; Lu Li; Hong Kang; Meixian Wang; Yanqun Liu; Guicun Wang; Ping Yu; Juan Liang; Zhen Liu (BMC Pregnancy and Childbirth)
Abstract Background and aims Recent studies have indicated possible links between the microbiota and the fetal heart, while the relevant mechanism is still unknown. This study is aims to investigate whether analyzing the microbiota and metabolic profiles of amniotic fluid collected from pregnant women whose fetuses with or without non-syndromic congenital heart defects (CHDs), during the second and third trimester of pregnancy, could offer valuable insights into CHDs. Methods and results A case-control study was conducted with 17 cases diagnosed with non-syndromic CHDs (CHDs group) and 34 controls without congenital anomalies (control group) at a ratio of 1:2. The 16 S rDNA gene sequencing and metabolomics methods were employed to assess 51 amniotic fluid samples. The amniotic fluid microbiome from the CHDs group exhibited significantly higher Shannon and Simpson indices compared to the control group. At the genus level, 240 bacterial taxa were substantially enriched in the two groups, with 93 of those taxa being highly enriched in the case group. Compared to the control group, the case group exhibited 177 metabolites that were significantly increased and 480 metabolites that were down-regulated. The differential metabolites were primarily enriched in the steroid hormone biosynthesis, bile secretion and ovarian steroidogenesis, according to KEGG analysis. The observed variations in nine metabolites could attributed to fifty-eight distinct bacterial taxa. The nine differential metabolites were mainly associated with pathways involving steroid hormone biosynthesis, bile secretion, glycolysis, tricarboxylic acid (TCA) cycle, NADPH metabolism, and acyl transfer pathways. Conclusion The CHDs group has disturbed amniotic fluid microbiota and metabolites, and more research was required to elucidate the mechanism.